Ionomic analysis, polyphenols characterization, analgesic, antiinflammatory and antioxidant capacities of Cistus laurifolius leaves: in vitro, in vivo, and in silico investigations - Aziz Zouhri; Toufik Bouddine; Naoual El Menyiy; Rabie Kachkoul; Yahya El-mernissi; Farhan Siddique; Rania moubachir; Farid Khallouki; Ahmad Mohammad Salamatullah; Gezahign Fentahun Wondmie; Mohammed Bourhia; Lhoussain Hajji (Scientific Reports, 2023)
Abstract This study aims to investigate the chemical and mineral composition, antioxidant, analgesic, and anti-inflammatory effects of the aqueous extract of Cistus laurifolius var. atlanticus Pit. (Cistaceae). Additionally, molecular docking interactions of various ligands with antioxidant protein target urate oxidase (1R4U) and anti-inflammatory protein target cyclooxygenase-2 (3LN1), revealing potential dual activities and highlighting specific residue interactions. The chemical characterization focused at first glance on the mineral composition which showed that C. laurifolius extract is a mineral-rich source of potassium (K), magnesium (Mg), manganese (Mn), sodium (Na), phosphorus (P), and zinc (Zn). We next performed, ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) analysis, the latter showed various polyphenols in C. laurifolius extract including Gallic acid as the predominant polyphenol. Isoquercetin, Taxifolin and Astragalin were also among the major flavonoids detected. The antioxidant capacity of C. laurifolius leaves was tested using 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1- picrylhydrazyl (DPPH) and reducing power (RP) assays. In vitro analysis of the anti-inflammatory property of C. laurifolius leaves was conducted by the albumin denaturation test and the in vivo was assessed in the sequel by carrageenan-induced paw edema test. The analgesic activity was evaluated in vivo using tail flick, acetic acid-induced contortion, and plantar tests. The findings showed that the leave extract had a powerful antioxidant activity with an IC50 values of 2.92 ± 0.03 µg/mL (DPPH) and 2.59 ± 0.09 µg/mL (in RP test). The studied extract strongly abolished the induced inflammation (82%). Albumin denaturation test recorded an IC50 value of 210 µg/mL. Importantly, the oral administration of C. laurifolius extract considerably reduced the nociceptive effect of acetic acid in rats, showing a significant analgesic effect in a dose-related manner. Altogether, our results showed that C. laurifolius can be a promising source of phytochemicals for drug development potential.